La povertà nei Balcani - Carlucci, Francesco; Carlucci, Stefano (Rivista di studi politici internazionali, 2008)
ABSTRACT - The paper shows the situation of poverty in the Balkan Countries, emphasizing the fact that its mean indicators, by which the level of poverty is calculated, can hide very different conditions of deprivation in the entities within a Country. This evidence is shown by means of two examples, one regarding Albania and another Bosnia and Herzegovina. The human conditions of the eight Balkan Countries is then determined in two years, 2000 and 2004, through fifteen indicators and using a probabilistic methodology of aggregation that has been developed by the Authors. On the base of these variables, related to the human condition of the Balkan Countries, the poverty in each is evaluated. RÉSUMÉ - L’article illustre la situation de pauvreté dans les Pays des Balkans et souligne le fait que les indicateurs utilisés peuvent cacher des conditions de pauvreté très différentes dans un même Pays. Ceci est montré par deux exemples, l’un qui concerne l’Albanie et l’autre qui regarde la Bosnie et Herzégovine. On détermine ensuite la condition humaine des huit Pays des Balkans dans deux moments temporels differents, les années 2000 et 2004, en employant une méthodologie probabiliste développée par les Auteurs. Sur la base des indicateurs relatifs à cette condition humaine on évalue ensuite le niveau de pauvreté dans chque Pays.